1992
DOI: 10.1111/j.1365-2621.1992.tb06870.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Aroma Volatiles of Orange Juice into Laminated Carton Packages Did Not Affect Sensory Quality

Abstract: Orange juice was stored in glass bottles and polyethylene/barrier material laminated cartons at 4°C for 24 wk. Studies were carried out on the absorption of 19 orange juice aroma compounds (e.g ethyl butyrate, d-limonene) into low density polyethylene (LDPE). Sensory evaluations were performed on the same orange juice in different packages over the storage period. A reduction of d-limonene of up to 50% by absorption into the LDPE inside coating was observed. However, an experienced sensory panel did not distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Recent research indicates that the adsorption of peel oil volatiles by film polymers may not affect the sensory quality of orange juices (12,13). It is therefore unlikely that differences in recoverable oil measurements affected sensory results of heated vs pressurized juices ( Table 1).…”
Section: Oil Concentrationmentioning
confidence: 96%
“…Recent research indicates that the adsorption of peel oil volatiles by film polymers may not affect the sensory quality of orange juices (12,13). It is therefore unlikely that differences in recoverable oil measurements affected sensory results of heated vs pressurized juices ( Table 1).…”
Section: Oil Concentrationmentioning
confidence: 96%
“…The sorption of components by the food packaging, has been the most studied interaction phenomenon regarding orange juice. It was established that several components like free fatty acids and aroma volatiles could be absorbed by the polymer from the orange juice (Pieper & Petersen, 1995;Pieper, Borgudd, Ackermann, & Fellers, 1992;Willige, Van Linssen, Legger-Huysman, & Voragen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Is the most abundant monocyclic monoterpene in nature and represents more than 90% of orange peel oil, being the most important residue in the citrus industry [12]. The limonene diffusion through packaging has been widely studied in different food contact materials such as polyethylene (PE) [13], low density polyethylene (LDPE) [14], high density polyethylene (HDPE), polystyrene (PS) [15] and PLA [15,16]. Furthermore, the sorption of aroma compounds through packaging materials have been reported recently by Salazar et al, (2012) [17], who found a plasticization effect of PLA films by aroma compounds after the sorption studies.…”
Section: Introductionmentioning
confidence: 99%